ESL IN THE EYES OF A MIDDLE-EASTERNER: A CRITICAL REPORT ON SECOND LANGUAGE LEARNING - Ariatna Ariatna (BAHAS, 2018)
This report is based on an ethnographic project which attempts to find out how someone learns a second language from a participant’s point of view. The participant was a male international student who studied in Adelaide, South Australia with a continuous experience of learning English as a second language for twelve consecutive years in his country. Using a self-designed questionnaire which is based on Spolky’s model of second language learning (1989, as cited in Mitchell & Myles, 2004, p. 8), information about the participant’s language use, learning and behaviour was gathered through a 45-minute face-to-face interview. While participation is voluntary, the confidentiality of the participant and any information provided by the participant is highly respected. The results showed that the participant’s learning experience seemed to accord with the contemporary notions of second language acquisition in relation to pronunciation, learning setting, motivation, teaching approach, and other cognitive or affective factors.